1991
DOI: 10.1002/nml.4130010305
|View full text |Cite
|
Sign up to set email alerts
|

How nonprofits adapt to a stringent environment

Abstract: Results from a survey of nonprofit human service agencies in Arizona are presented. Most agencies reported steady or declining revenues, increased competition with other agencies, and rising demand for services from clients who cannot pay. The strategies used to adapt to these changes ranged from small‐scale productivity enhancements to responses involving a complete restructuring of the agency as well as cutbacks in client services. The discussion focuses on the implications of the results for the continued v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 4 publications
0
34
0
Order By: Relevance
“…During the Reagan years, the federal government cut the budgets of social programs and shifted to block grant funding for states (Abrahamson and Salamon, 1986). Human service nonprofits that were heavily dependent on such funding responded to the loss by creating revenue-generating programs and redirecting their efforts to state and local sources of funding (Liebschutz, 1992;McMurtry, Netting, and Kettner, 1991). This "marketization" of nonprofits became the trend of the decade (Salamon, 1997).…”
Section: Strategic Responses To the 1980smentioning
confidence: 96%
See 1 more Smart Citation
“…During the Reagan years, the federal government cut the budgets of social programs and shifted to block grant funding for states (Abrahamson and Salamon, 1986). Human service nonprofits that were heavily dependent on such funding responded to the loss by creating revenue-generating programs and redirecting their efforts to state and local sources of funding (Liebschutz, 1992;McMurtry, Netting, and Kettner, 1991). This "marketization" of nonprofits became the trend of the decade (Salamon, 1997).…”
Section: Strategic Responses To the 1980smentioning
confidence: 96%
“…Additional studies indicated that human service nonprofits responded by cutting programs and services to the poor (Grønbjerg, 1988); by "increasing efforts to gain media attention to increase charitable donations" (McMurtry, Netting, and Kettner, 1991, p. 244); by expanding networks with other agencies; and by greater productivity with current resources through increasing staff workloads and relying more on volunteers (McMurtry, Netting, and Kettner, 1991). Organizations recruited board members who brought fundraising abilities and skills to the organization, and they…”
Section: Strategic Responses To the 1980smentioning
confidence: 97%
“…During the Reagan era, when federal government grants were cut by 20%, this "partnership was disrupted" and the sector lost more than $30 billion in funding. (p. xiii) Nonprofits responded to the loss in revenue by terminating programs and staff, reducing overhead, and redirecting their efforts to state and local governments (Liebschutz, 1992;McMurtry, Netting, Kettner, & Kettner, 1991). Today, nonprofits in the area of human services continue to receive approximately 40% of their budgets from government (Gronbjerg, Kimmich, & Salamon, 1995;O'Connell, 1996).…”
Section: Survival Strategies Of Social Service Organizations Under Wementioning
confidence: 99%
“…In their study of nonprofit human service agencies, McMurtry et al (1991) contend that privatization of services has improved the range and quality of services available to contract eligible and full-pay clients, but has reduced the capacity of the system to serve the working poor-people not poor enough for public assistance but not affluent enough to pay for services. (p. 250) Studies have found that welfare reform, and the work-first approach, contributes to the growing population of working poor who now commonly compose the clientele of many nonprofit organizations (Edin & Lein, 1997;Gault, Hartmann, & Yi, 1998).…”
Section: The Hollow Statementioning
confidence: 99%